Implementation of Delayed Cord Clamping for 3 Min During Term Cesarean Sections Does Not Influence Maternal Blood Loss - Celen, Stefanie; Horn-Oudshoorn, Emily J. J.; Knol, Ronny; Wilk, Eline C. van der; Reiss, Irwin K. M.; DeKoninck, Philip L. J. (Frontiers in Pediatrics, 2021)
Objective: To assess maternal and neonatal safety outcomes after a local protocol adjustment to change the interval of cord clamping to three minutes after term caesarean section. Design, Setting and Patients: We performed a retrospective cohort study in a tertiary referral hospital (Erasmus MC, Rotterdam). We included pregnant women who gave birth at term after caesarean section. A cohort (Nov 2016–Oct 2017) prior to the protocol implementation was compared to a cohort after its implementation (Dec 2017–Dec 2018). The study population covered 789 women (n=413 post-cohort; n=376 pre-cohort). Interventions: Implementation of a local protocol changing the interval of cord clamping to three minutes in all term births. Main outcome measures: Primary outcomes were the estimated maternal blood loss and the occurrence of postpartum hemorrhage (blood loss >1000ml). Secondary outcomes included both maternal as well as neonatal outcomes. Results: In the post-cohort group delayed cord clamping for three minutes was performed in 70% (N=291); in the pre-cohort group immediate cord clamping was performed in 100%. Estimated maternal blood loss was not significantly different between the two groups (400 ml versus 400 ml; p=0.52). The incidence of postpartum hemorrhage (OR 1.24, 95%CI 0.73-2.11) and maternal blood transfusion (OR 1.33, 95%CI 0.56-3.14) were not different. Neonatal hematocrit levels were higher after delayed cord clamping (0.55% versus 0.51%; p=0.01) but need for phototherapy was not significantly different (OR 1.95, 95%CI 0.99-3.84). Conclusion: Implementation of delayed cord clamping for three minutes in term caesarean sections was not associated with increased maternal bleeding complications.